Shiva Linga in the Garbhagriha of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The interiors of the garbhagriha (sanctum sanctorum) of the Suhaveshwar Temple are seen here. It is square in plan and has a Shiva linga (aniconic representation of Shiva) at its centre as the object of worship. The Shiva linga is placed on a high pedestal that has ornate mouldings.